2005
DOI: 10.1113/jphysiol.2004.081422
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of skeletal and cardiac voltage‐gated sodium channels by calmodulin

Abstract: Calmodulin (CaM) has been shown to modulate different ion channels, including voltage-gated sodium channels (NaChs). Using the yeast two-hybrid assay, we found an interaction between CaM and the C-terminal domains of adult skeletal (Na V 1.4) and cardiac (Na V 1.5) muscle NaChs. Effects of CaM were studied using sodium channels transiently expressed in CHO cells. Wild type CaM (CaM WT ) caused a hyperpolarizing shift in the voltage dependence of activation and inactivation for Na V 1.4 and activation for Na V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 49 publications
3
91
0
Order By: Relevance
“…Interestingly, some of the effects of R1916G may also be caused in part by the inhibition of the binding of calmodulin. In fact, it has been shown that calmodulin can differentially modulate several Na + channel isoforms, inducing functional effects that depend on the isoform and on the cell type used for the experiments (Young and Caldwell, 2005;Choi et al, 2006;Biswas et al, 2008). However, both reduction of cell surface expression and negative shift of the inactivation curve, which are two of the effects caused by R1916G, have been observed blocking the binding of calmodulin to Na + channels (Choi et al, 2006;Biswas et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some of the effects of R1916G may also be caused in part by the inhibition of the binding of calmodulin. In fact, it has been shown that calmodulin can differentially modulate several Na + channel isoforms, inducing functional effects that depend on the isoform and on the cell type used for the experiments (Young and Caldwell, 2005;Choi et al, 2006;Biswas et al, 2008). However, both reduction of cell surface expression and negative shift of the inactivation curve, which are two of the effects caused by R1916G, have been observed blocking the binding of calmodulin to Na + channels (Choi et al, 2006;Biswas et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…1C), is an important residue of the calmodulin binding IQ motif (Bahler and Rhoads, 2002), which is implicated in the modulation of several Na + channel isoforms (Young and Caldwell, 2005;Choi et al, 2006;Biswas et al, 2008), and we have shown that calmodulin can rescue hNa v 1.1-M1841T (Rusconi et al, 2007). Although R1916G should inhibit calmodulin binding, we tested the effect of cotransfection of calmodulin and found, indeed, that there was no significant modification of hNa v 1.1-R1916G current density ( Fig.…”
Section: Effects Of Other Interacting Proteinsmentioning
confidence: 99%
“…Excitability of the membrane is determined by the number of Na channels and by the fraction of them that is not inactivated. Two isoforms of the poreforming ␣ subunit of the sodium voltage-gated channels, Nav 1.4 and Nav 1.5, also indicated as SKMI and SKMII, are expressed in skeletal muscle (136) in association to the ubiquitous ␤-1 subunit and exhibit different electrophysiological properties (890). Expression of Nav 1.5 is restricted to immature and denervated muscles (389), while Nav 1.4 is expressed in adult muscles both in slow and fast fibers.…”
Section: Ionic Channels and Membrane Excitabilitymentioning
confidence: 99%
“…The C-terminus of all VGSC contains a conserved IQ motif (Herzog et al 2003b;Mori et al 2000;Rhoads and Friedberg 1997). CaM has been shown to regulate current densities and gating properties of several sodium channels (Na v 1.2, Na v 1.4, Na v 1.5, and Na v 1.6) but, importantly, this channel modulation is isoform dependent (Deschenes et al 2002;Herzog et al 2003b;Kim et al 2004;Tan et al 2002;Young and Caldwell 2005). For example, the substitution of IQ with glutamic acid residues (EE) in Na v 1.6, which blocks CaM binding, causes a hyperpolarizing shift of steady-state inactivation and a twofold slower fast inactivation, whereas these properties remain unchanged in Na v 1.4IQ/EE (Herzog et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Calmodulin (CaM) binds directly to ion channel target proteins by the isoleucine-glutamine (IQ) motif (Rhoads and Friedberg 1997), in a Ca 2ϩ -independent manner (Erickson et al 2001;Kim et al 2004;Mori et al 2000;Xia et al 1998), and has been shown to regulate current density and biophysical properties of sodium channels (Deschenes et al 2002;Herzog et al 2003b;Kim et al 2004;Tan et al 2002;Young and Caldwell 2005). The C-terminus of all VGSC contains a conserved IQ motif (Herzog et al 2003b;Mori et al 2000;Rhoads and Friedberg 1997).…”
Section: Introductionmentioning
confidence: 99%